Pengaruh Terapi Musik Gamelan Terhadap Ekspresi Wajah Positif Pada Anak Autis - Erwin Dian Sartika; Faridah Ainur Rohmah (Jurnal Psikologi Integratif, 2013)
ABSTRACT The purpose of this research was to study the influence of Javanese tradition music therapy (gamelan) on positive face expression of autistic child. The research subject were three children of autism. Method of this research used observation with rating scale. The research subject was selected by purposive sampling. The data analysis used Friedman-test. The result of analysis was chi square (X2)= 6 (p